Ring-opening polymerization of lactide using salen–aluminum complexes bearing Schiff-base ligands derived from cis-1, 2-cyclohexanediamine. Issue 4 (16th February 2016) - Cui, Yuan; Li, Dongni; Gao, Bo; Zhou, Yuqi; Chen, Li; Qiu, Baoguo; Li, Yanhui; Duan, Qian; Hu, Ninghai
Abstract: Three aluminum complexes supported by salen ligands derived from cis -1, 2-cyclohexanediamine and salicylaldehyde derivatives were synthesized. They were characterized by 1 H, 13 C NMR spectra, and elemental analysis. X-ray diffraction analysis revealed that aluminum was in distorted square pyramidal geometry in2 . These complexes were employed as catalysts for the ring-opening polymerization (ROP) of L-lactide and rac -lactide. Complex2 showed the highest activity among these complexes with isopropanol for the ROP of L-lactide and3 showed the highest stereoselectivity for the ROP of rac -lactide attaining partially isotactic polylactide with a P m of 0.75. The kinetic data of the polymerization utilizing3 as catalyst showed that the polymeric rate was first order to the monomer and catalyst. Abstract :